Comparisons of special education teachers and faculty’s perceptions of employing augmented reality for pupils with intellectual disabilities - Algethami, Rasheed Khuwayshan (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of the current study is to investigate the comparisons between faculty and special education teachers’ views of the use of augmented reality with learners with intellectual disabilities. In recent years, the Saudi education minister has made many reforms to advance the use of assistive technology in the teaching of learners with intellectual disabilities. The design of descriptive research was methodologically used to gather data from a hundred and sixty-five faculty members from Taif University and ninety special education teachers from Taif schools through an electronic survey. The questionnaire is divided into two parts: the first part includes demographic variables, namely gender and academic experiences. The second part included statements that focused on the views of special education teachers and faculty members regarding the use of AR technology for students with ID. The findings showed that faculty have more agreeable perceptions compared to special education instructors in Saudi Arabia. Also, there was a significant impact on special education teachers’ perceptions of using augmented reality for students with intellectual disabilities based on gender. However, years of teaching experiences did not impact the special education teachers and faculty perceptions of using augmented reality with students with intellectual disabilities. Thus, the implication of the study recommends that special education teachers and faculty members should be more exhibited in training courses emphasizing raising awareness on the utilization of augmented reality for students with intellectual disabilities within general and university education.